2005
DOI: 10.1111/j.1365-2796.2005.01531.x
|View full text |Cite
|
Sign up to set email alerts
|

Metformin improves endothelial function in patients with metabolic syndrome

Abstract: Background. Metabolic Syndrome (MS) is associated with impaired endothelial function and increased cardiovascular risk. Insulin resistance is a key feature of MS and plays an important role in the pathogenesis of endothelial dysfunction. Aim of the present study was to evaluate the effect of metformin on endothelial function and insulin resistance, assessed by the homeostasis model (HOMA-IR, homeostasis model assessment-insulin resistance), in patients with MS. Methods. Sixty-five subjects (37 men and 28 women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
119
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(131 citation statements)
references
References 44 publications
7
119
1
4
Order By: Relevance
“…17,[23][24][25][26] In the current study, a 1-year combined program of intensive lifestyle Abbreviations: BP, blood pressure; DBP, diastolic blood pressure; SBP, systolic blood pressure. During salt-sensitivity testing, subjects were first exposed to 1 week of a high-salt diet followed by a week of a low-salt diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,[23][24][25][26] In the current study, a 1-year combined program of intensive lifestyle Abbreviations: BP, blood pressure; DBP, diastolic blood pressure; SBP, systolic blood pressure. During salt-sensitivity testing, subjects were first exposed to 1 week of a high-salt diet followed by a week of a low-salt diet.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated above caloric restriction, increase physical activity and metformin have been shown independently to reduce cardiovascular risk factors and the development of type II diabetes. 17,[23][24][25][26] However, the lifestyle interventions have been shown to be more effective than metformin in preventing development of type II diabetes mellitus. 26 A substantial body of evidence supports the concept that pre-hypertension and hypertension are associated with obesity; however, the reason for this association in still controversial, and may be multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin has been also shown to improve endotheliumdependent vasodilation in rats (27) and in patients with type 2 diabetes (28). Additionally, it has been recently shown that in subjects with metabolic syndrome, metformin improved flow-mediated vasodilation of the brachial artery (29).…”
Section: Vascular Changesmentioning
confidence: 99%
“…It also decreases hepatic output of glucose [36]. Moreover, metformin decreases β-cells apoptosis and slows diabetes disease progression [37][38][39]. Many of these effects are mediated through AMP-kinase pathway [22,23,30].…”
Section: Discussionmentioning
confidence: 99%